PEMBUATAN DAN PENYIARAN APLIKASI KONTEN PORNOGRAFI DALAM PANDANGAN KRIMINOLOGI - Oktaviona, Oktaviona; Hermansyah, Hermansyah; Hertini, Mega Fitri (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract Nowadays, the spread of pornographic content is increasingly common. Unofficial applications and sites can circulate freely on the internet network, both national networks andinternational networks. Efforts are being made to block sites and applications withpornographic content, but they still cannot stop the emergence of similar applications andsites. Like the HotLive application which was previously called Bling Bling. An applicationthat has been blocked by KOMINFO but is still launching a similar application with policies that are not much different. The problem formulation in this research is